Application of copperas and sago starch in domestic wastewater treatment by coagulation flocculation proces - Kamar, Wan Izatul Saadiah Wan (Universiti Sains Malaysia, 2016)
Conventional treatment of domestic wastewater involves various processes which include physical, chemical and biological method. Coagulation and flocculation is one of the methods normally applied for water and wastewater treatment. In this study, copperas (CPP) and sago starch (SG) were used as coagulant. CPP used is a by-product of one of an ilmenite processing factories in Malaysia. Previously, it has been dumped in the landfill, untreated. The characteristics and its potential in treating domestic wastewater were investigated and the performances were compared with analytical ferrous sulfate (AFS). SG is a common starch commercially available. It has been used in food, biotechnology and cosmetic industries. Its usage as coagulant in domestic wastewater treatment has not been investigated to date. The domestic wastewater used in this research was collected from Juru Regional Sewage Treatment Plant (JRSTP) at Juru, Penang, Malaysia. Sampling process was conducted for one year (April 2014 to April 2015). The raw sample contains high concentration of COD, turbidity, suspended solids, ammoniacal nitrogen and colour. In this study, both coagulants (CPP and SG) were examined in standard jar test method. The optimum experimental conditions for CPP was pH 9, 150 mg/L of dosage with 1 min of rapid mixing (100 rpm), 20 mins of slow mixing (60 rpm) and 18 mins of settling. For test using SG, the optimum conditions occurred at pH 7, 2000 mg/L of dosage with 1 min of rapid mixing (100 rpm), 30 mins of slow mixing (20 rpm) and 18 mins of settling. It was found that, CPP removed 88% of turbidity, 79% of colour, 92% of suspended solids, 83% of COD, 98% of phosphorus, 24% of ammonia and 44% of TKN. On the other hand, AFS removed 83% of turbidity, 82% of colour, 95% of suspended solids, 79% of COD, 99% of phosphorus, 16% of ammonia and 12% of TKN. Besides that, the treatment using SG obtained the removal of 82% of turbidity, 71% of colour, 82% of suspended solids, 73% of COD, 57% of phosphorus, 38% of TKN and 6% of ammonia. As a conclusion, CPP, AFS and SG have good potential to be used as coagulant in domestic wastewater treatment.